Audio Feedback Project: A Project to Increase Social Presence in a Virtual Library and Knowledge Service - Holland, Matt (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2022)
Objective – This research project sought to determine if audio feedback in literature searches can increase the social presence of the library and create a positive view of the library service. It also explored the process of recording and sending audio feedback; tested its practicality, sustainability, and accessibility; and ascertained whether audio feedback enhanced the library’s communication, thereby creating a positive attitude toward the library and its services.Methods – The research was conducted in a small virtual library and information service. The research sample consisted of all library users and clinicians who requested a mediated literature search between July 2019 and July 2020. All participants were sent an audio commentary on their search results, recorded by the librarian, and were asked to respond to an online questionnaire. The questionnaire consisted of five statements. The study participants indicated their agreement or disagreement with each statement on a five-point Likert scale.Results – The researcher sent out 96 audio commentaries, generating 31 responses to the questionnaire. The results indicated that users felt the audio feedback improved their understanding of the results of their inquiry, made them feel more comfortable about using the library, enhanced their experience of communicating with the library and provided a better experience than just receiving an email. The responses broadly supported the contention that audio commentaries created social presence and generated a positive view of the library.Conclusion – The researcher found that delivering audio feedback was both practical and sustainable. Some consideration was given to individual learning styles and how these made audio or text feedback more or less effective. Specifically, audio feedback enhanced communications better than an email alone.